Upaya Peningkatan Hasil Belajar Biologi pada Materi Sistem Eksresi Manusia dengan Model Pembelajaran Langsung dan Pendekatan Flipped Classroom Siswa Kelas XI-B SMA Negeri 4 Palu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This research is motivated by the low learning outcomes of students in class XI-B at SMA Negeri 4 Palu, which are still below the Minimum Completeness Criteria (KKM) set at 75. The aim of this study is to improve the learning outcomes of students through the application of direct learning models with a Flipped Classroom approach. This research is a Classroom Action Research (CAR) conducted in two cycles during the 2023/2024 academic year with the subjects consisting of 36 students from class XI-B at SMA Negeri 4 Palu. The data collection methods used include observations and learning outcome tests. The research instruments consist of pretest and posttest questions on the topic of the Human Excretory System. The results of the study indicate that the application of the direct learning model with the Flipped Classroom approach can improve students' Biology learning outcomes. In the pre-cycle, there were 11 students who reached the KKM, with a classical completeness percentage of 30.56%. In Cycle I, the number of students achieving KKM increased to 24, with a classical completeness percentage of 66.67%. In Cycle II, the number of students reaching KKM increased further to 31, with a classical completeness percentage of 86.11%. Based on these results, it can be concluded that the application of the direct learning model with the Flipped Classroom approach is effective in improving the Biology learning outcomes of students in class XI-B at SMA Negeri 4 Palu on the topic of the Human Excretory System